Psikologi Komunikasi Dalam Dakwah Pada Lansia (Studi Kasus Majelis Ta’lim An-Nuriyyah, Waru, Sidoarjo) - Maimunah; Lucky Prihartanto (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
This study examines the communication psychology underlying the da'wah practice of Bu Nyai Ati' Nursyafa'ah at Majelis Ta'lim An-Nuriyyah, Waru, Sidoarjo, a congregation composed predominantly of women aged sixty to eighty-three. Using a descriptive qualitative design with a phenomenological method, data were gathered through participant observation, an in-depth interview with the preacher, and structured interviews with twenty congregants, then analyzed through Rakhmat's (2015) framework of communicator, communicant, and message psychology. Findings show that twenty-seven years of consistent presence produced layered credibility, similarity-based attraction, and informal charismatic authority (Hovland & Weiss, 1951; Kelman, 1958), while the personal, sociopsychological, and situational needs of elderly listeners were deliberately managed, and bilingual, multisensory, multi-layered messages addressed cognitive, affective, and conative dimensions simultaneously. Six interlocking mechanisms, trust, psychological safety, relevance, communal reinforcement, cathartic prayer, and internal opinion leadership, explain this success, demonstrating that competency-based authority outweighs age-based hierarchy in elderly-focused da'wah.